An Estimator for UAV Attitude Determination based on Accelerometers, GNSS Sensors, and Aerodynamic Coefficients. Issue 3 (27th August 2018) - de Celis, Raúl; Cadarso, Luis
Abstract: Accurate navigation and control of Unmanned Air Vehicles (UAV) are strongly linked to the estimation of position and attitude. Rotation of an aircraft can be determined measuring two vectors, for example, velocity and gravity vectors, in two independent reference frameworks, for example, inertial and the body reference frames. The velocity vector can be determined in inertial reference frame from a GNSS‐based sensor and in the body reference frame by integrating accelerometer measurements. A novel approach is presented for gravity vector estimation in the body reference frame, which is based on UAV aerodynamics and mass properties. Combining both vectors enables determination of body rotation. Nonlinear simulations show that, utilizing GNSS sensors, strap‐down accelerometers and the proposed approach, aircraft attitude determination is accurate. The developed calculations are implemented on a fixed‐wing UAV, permitting the substitution of specific attitude determination gadgets, which are normally costly for several applications. © 2018 Institute of Navigation.